Chemical Modifications of Cassava Peel as Adsorbent Material for Metals Ions from Wastewater - Daniel Schwantes; Affonso Celso Gonçalves; Gustavo Ferreira Coelho; Marcelo Angelo Campagnolo; Douglas Cardoso Dragunski; César Ricardo Teixeira Tarley; Alisson Junior Miola; Eduardo Ariel Völz Leismann (Journal of Chemistry)
Residues from the processing of cassava roots (Manihot esculenta Crantz), or cassava peels, are evaluated as chemically modified adsorbents with H2O2, H2SO4, and NaOH, in the removal of metal ions Cd(II), Pb(II), and Cr(III) from contaminated water. Modified adsorbents were chemically characterized for their chemical composition and pHPZC (point of zero charge), while adsorption tests determined the best conditions of pH, adsorbent mass, and contact time between adsorbent and adsorbate in the process of removal of the metal ions. Isotherms obtained from the preliminary results were linearized by Langmuir’s and Freudlich’s models. The thermodynamic parameters, such as ΔH, ΔG, and ΔS, were also evaluated. The modifying solutions proposed were effective in the modification of adsorbents and resulted in high capacity sorption materials. Equilibrium time between adsorbent and adsorbate for the solutions contaminated with metals is about 40 minutes. The Langmuir model adjusted to most results, indicating monolayers adsorption of Cd(II), Pb(II), and Cr(III). The values obtained for Langmuir Qm show a higher adsorption capacity caused by chemical modifications, with values such as 19.54 mg Cd(II) per g of M. NaOH, 42.46 mg of Pb(II) per g of M. NaOH, and 43.97 mg of Cr(III) per g of M H2O2. Results showed that modified cassava peels are excellent adsorbent, renewable, high availability, and low-cost materials and a feasible alternative in the removal of metals in industries.